The Influence of Perceived Ease, Perceived Risk, System Security, and Service Quality on Trust in Transactions Using Shopee E-commerce - Nurikmah, Tri; Mudjiyanti, Rina; Santoso, Suryo Budi; Amir (Mahameru Publisher, 2023)
The rapid development of information technology has an impact on the transaction style of Indonesian society. This has led to the emergence of online transaction activities. This research has the purpose to prove whether there is an influence of perceived ease, perceived risk, system security, and service quality on trust in transacting using Shopee e-commerce. The research sample consists of students at Muhammadiyah University of Purwokerto, with the condition that these students are users of Shopee e-commerce and have transacted at least once. The purpose is to assess the factors of using Shopee e-commerce from the perspective of students. The analysis results indicate that perceived ease, system security, and service quality have a significant positive influence on trust in transacting using Shopee e-commerce. Meanwhile, perceived risk has a significant negative impact on trust in transacting using Shopee e-commerce.